Activity of the Brassinosteroid Transcription Factors BRASSINAZOLE RESISTANT1 and BRASSINOSTEROID INSENSITIVE1-ETHYL METHANESULFONATE-SUPPRESSOR1/BRASSINAZOLE RESISTANT2 Blocks Developmental Reprogramming in Response to Low Phosphate Availability . Issue 2 (18th August 2014) - Singh, Amar Pal; Fridman, Yulia; Friedlander-Shani, Lilach; Tarkowska, Danuse; Strnad, Miroslav; Savaldi-Goldstein, Sigal
Abstract : Pi deprivation shifts the subcellular distribution of two key brassinosteroid-related transcriptional effectors to trigger shallower root system architecture . Abstract: Plants feature remarkable developmental plasticity, enabling them to respond to and cope with environmental cues, such as limited availability of phosphate, an essential macronutrient for all organisms. Under this condition, Arabidopsis ( Arabidopsis thaliana ) roots undergo striking morphological changes, including exhaustion of the primary meristem, impaired unidirectional cell expansion, and elevated density of lateral roots, resulting in shallow root architecture. Here, we show that the activity of two homologous brassinosteroid (BR ) transcriptional effectors, BRASSINAZOLE RESISTANT1 (BZR1) and BRASSINOSTEROID INSENSITIVE1-ETHYL METHANESULFONATE-SUPPRESSOR1 (BES1)/BZR2, blocks these responses, consequently maintaining normal root development under low phosphate conditions without impacting phosphate homeostasis. We show that phosphate deprivation shifts the intracellular localization of BES1/BZR2 to yield a lower nucleus-to-cytoplasm ratio, whereas replenishing the phosphate supply reverses this ratio within hours. Phosphate deprivation reduces the expression levels of BR biosynthesis genes and the accumulation of the bioactive BR 28-norcastasterone. In agreement, low and high BR levels sensitize and desensitize root response to this adverse condition, respectively. Hence, we propose that the environmentally controlled developmental switch from deep to shallow root architecture involves reductions in BZR1 and BES1/BZR2 levels in the nucleus, which likely play key roles in plant adaptation to phosphate-deficient environments.